2019
DOI: 10.1002/chem.201902771
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid‐Derived Sensors for Specific Zn2+ Detection Using Hyperpolarized 13C Magnetic Resonance Spectroscopy

Abstract: Alterations in Zn2+ concentration are seen in normal tissues and in disease states, and for this reason imaging of Zn2+ is an area of active investigation. Herein, enriched [1‐13C]cysteine and [1‐13C2]iminodiacetic acid were developed as Zn2+‐specific imaging probes using hyperpolarized 13C magnetic resonance spectroscopy. [1‐13C]cysteine was used to accurately quantify Zn2+ in complex biological mixtures. These sensors can be employed to detect Zn2+ via imaging mechanisms including changes in 13C chemical shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Zum spezifischen Zn 2+ -Nachweis wurden [1-13 C]-Cystein und [1- 13 C 2 ]-Iminodiessigsäure als molekulare Sonden entwickelt. [63] 15 N-o-Aminophenol-N,N,O-triessigsäure ( 15 N-APTRA; Abbildung 6C)i st ein langlebiger hyperpolarisierter Ca 2+ -Chelator. [60] Das kleine gyromagnetische Verhältnis des 15 N-Kerns trägt zum relativ großen T 1 -Wert bei (37 so hne Ca 2+ und 36 sm it Ca 2+ bei 9.4 T).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Zum spezifischen Zn 2+ -Nachweis wurden [1-13 C]-Cystein und [1- 13 C 2 ]-Iminodiessigsäure als molekulare Sonden entwickelt. [63] 15 N-o-Aminophenol-N,N,O-triessigsäure ( 15 N-APTRA; Abbildung 6C)i st ein langlebiger hyperpolarisierter Ca 2+ -Chelator. [60] Das kleine gyromagnetische Verhältnis des 15 N-Kerns trägt zum relativ großen T 1 -Wert bei (37 so hne Ca 2+ und 36 sm it Ca 2+ bei 9.4 T).…”
Section: Methodsunclassified
“…Es wurde auch demonstriert, dass hyperpolarisierte 13 C‐markierte EGTA μ m Konzentrationen an Ca 2+ in vitro nachweisen kann. Zum spezifischen Zn 2+ ‐Nachweis wurden [1‐ 13 C]‐Cystein und [1‐ 13 C 2 ]‐Iminodiessigsäure als molekulare Sonden entwickelt [63] …”
Section: Molekulare Dnp‐nmr‐sondenunclassified
“…In cells and live tissue slices, TPA removes zinc from fluorescence sensors more than twice as fast as TPEN [ 93 ]. The lower cellular toxicity associated with TPA makes it attractive for studies in a wide variety of biological contexts [ 48 , 94 , 95 , 96 , 97 , 98 ]. Although there is some evidence that TPA chelates metal ions other than zinc(II), particularly copper(I), it does not appear to substantially affect the concentrations of these ions at the less toxic and membrane‐permeable levels where it has typically been applied [ 99 , 100 ].…”
Section: Chemical Tools To Intercept Mobile Zincmentioning
confidence: 99%
“…It was also confirmed that hyperpolarized 13 C‐labeled EGTA can detect μ m levels of Ca 2+ in vitro. As for Zn 2+ , [1‐ 13 C] cysteine and [1‐ 13 C 2 ] iminodiacetic acid were developed as molecular probes for specific Zn 2+ detection [63] …”
Section: Dnp Nmr Molecular Probesmentioning
confidence: 99%